EFL Students’ Perceptions on Duolingo: How AI can Eliminate Socioeconomic Discrepancies - Listiana Ikawati; Az Zahra Rahimi; Farkhana Khairunnisa; Muhammad Iqbal Fauzan; Siska Rahayu (Universitas Islam Negeri (UIN) Mataram, 2022)
Different educational achievements between students from high socioeconomic status and those from lower socioeconomic status in universities are said to be caused by unequal access to learning resources. This research aimed at investigating students’ perspectives on the use of Duolingo in EFL learning to eliminate socioeconomic discrepancies in the university. This research used a descriptive qualitative design. Interviews were used to gather data from one male and two female higher education students majoring in the English Language Education program. This research shows two main findings. First, students have positive attitudes and enjoyable experiences in using Duolingo contributed by its fun, easy, accessible, and fun nature. Second, Duolingo, offering free charge for all users, can eliminate socioeconomic discrepancies among students in the university because it can be accessed by students from any socioeconomic condition. It implies that Duolingo as an AI tool can be used by both educators and students around the world as an accessible language teaching and learning resource. Therefore, there is a need to develop students’, educators’, and parents’ awareness of the utilization of Duolingo as a solution for the limited access to learning resources due to socioeconomic barriers.